Edukasi Mencuci Tangan yang Baik dan Benar dalam Peningkatan Kemandirian Anak Berkebutuhan Khusus - Lumbanraja, Hana Maria Uli; Mallisa, Hilda Emma; Unja, Ermeisi Er (Institute Of Advanced Knowledge and Science, 2024)
Children with special needs often face challenges in implementing daily living skills, including hygiene habits such as hand washing. In orphanages, they may not always receive enough individualized attention to learn and master this skill. The purpose of this community service activity is to provide education in the form of knowledge and procedures for proper hand washing and improve the skills of children with special needs so that they can independently wash their own hands. This community service activity uses an individual or small group approach with a direct demonstration method and uses audiovisual aids such as videos and posters. The results of this community service obtained an increase in the knowledge of children with special needs in hand washing skills as many as 9 children (30%) in the category of good independence ability, 18 children (60%) in the category of sufficient independence ability, and 3 children (10%) in the category of less independence ability. It is hoped that this education can be carried out regularly, especially for orphanage assistants. Thus it can further improve the knowledge and skills of children with special needs in washing hands independently to build clean and healthy living habits.